Marked alterations of neutrophil functions during sepsis‐induced immunosuppression. Issue 6 (29th July 2015) - Demaret, Julie; Venet, Fabienne; Friggeri, Arnaud; Cazalis, Marie‐Angélique; Plassais, Jonathan; Jallades, Laurent; Malcus, Christophe; Poitevin‐Later, Francoise; Textoris, Julien; Lepape, Alain; Monneret, Guillaume
Abstract : Neutrophil phenotypic, functional, and morphological alterations during sepsis‐induced immunosuppression suggest a deleterious role during post‐sepsis immune reprogramming. Abstract : Severe septic syndromes deeply impair innate and adaptive immunity and are responsible for sepsis‐induced immunosuppression. Although neutrophils represent the first line of defense against infection, little is known about their phenotype and functions a few days after sepsis, when the immunosuppressive phase is maximal (i.e., between d 3 and 8). The objective of the present study was to perform, for the first time, a global evaluation of neutrophil alterations in immunosuppressed septic patients (at d 3–4 and d 6–8) using phenotypic and functional studies. In addition, the potential association of these parameters and deleterious outcomes was assessed. Peripheral blood was collected from 43 septic shock patients and compared with that of 23 healthy controls. In the septic patients, our results highlight a markedly altered neutrophil chemotaxis (functional and chemokine receptor expressions), oxidative burst, and lactoferrin content and an increased number of circulating immature granulocytes (i.e., CD10 dim CD16 dim ). These aspects were associated with an increased risk of death after septic shock. In contrast, phagocytosis and activation capacities were conserved. To conclude, circulating neutrophils present with phenotypic, functional, and morphologic alterations a few days after sepsis onset. These dysfunctions might participate in the deleterious role of sepsis‐induced immunosuppression. The present results open new perspectives in the mechanisms favoring nosocomial infections after septic shock. They deserve to be further investigated in a larger clinical study and in animal models recapitulating these alterations.